Magical Realism in The Novel “Langgam Nyi Bagelen” by Yusuf Mahessa Dewo Pasiro and its Utilization as Learning Materials in Highschool - Anissa Julia Restanty; Furoidatul Husniah; Inno Cahyaning Tyas (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study examines magical realism in the novel Langgam Nyi Bagelen by Yusuf Mahessa Dewo Pasiro. The purpose of the study is to explain that magical and sacred things are not something new and considered unusual, but have different thoughts. The magical world and reality are two elements side by side. This type of research is qualitative. The research design used is a sociological literary approach with theory magical realism from Wendy B. Faris. Data acculumation techniques used documentation and data analysis with descriptive analysis. The Langgam Nyi Bagelen novel leads to the flow of magical realism literature by containing the legend of Nyi Bagelen and the Bagelen culture. The results and discussion of the study show that the novel contains characteristics from Wendy B. Faris consisting of illogical elements (irreducible elements), real world elements (phenomenal world), disturbing doubt elements (unsettling doubt), mixed elements of the real and magical worlds (merging realism), and elements of disruptions to time, space, and identity (disruptions of time, space, and identity). The five characteristics of magical realism in the Langgam Nyi Bagelen novel can be used as a means of cultural expression. This study provides knowledge about the magical elements found in novels that can reflect the social life of society and authors who use magical realism narratives to highlights social and political issues.